Answer:
z = -11, z = -2
Explanation:
Given that, (
) and (
), set up an equation that puts the first value of (
) equal to the other given value of the function.
![f(z)=√(z+27)-z=7](https://img.qammunity.org/2022/formulas/mathematics/college/lbmzmwty0gmd72k8uu3mfclkl6nywtqsis.png)
Use inverse operations to solve,
![√(z+27)-z=7\\\\√(z-27)=7+z\\\\z+27 = (7+z)^2\\\\z + 27 = 49+14z+z^2\\ -(27+z)\\\\0 = z^2+13z+22](https://img.qammunity.org/2022/formulas/mathematics/college/qpo0h8y9k5xnjygtyrbu59kshuohr0mnge.png)
Factor,
![0=(z+11)(z+2)](https://img.qammunity.org/2022/formulas/mathematics/college/n0kzqt68ejautqvhc8ozlydm4wmns12c0l.png)
Solve using the zero product property, the zero product property states that any number times zero equals zero;
![z=-11,z=-2](https://img.qammunity.org/2022/formulas/mathematics/college/n696h4ia8m5mnxibbwfaqc4pxs6gf1axph.png)